Local attitudes towards tourism and conservation in rural Botswana and Rwanda. Issue 1 (2nd January 2018) - Black, Rosemary; Cobbinah, Patrick Brandful
Abstract : The establishment of protected areas is an accepted means of achieving biodiversity conservation and associated tourism development; yet, there is limited evidence of the relationship between the two and how this influences local communities' attitudes to conservation and tourism. Joint venture models are one way to achieve these two outcomes. The African Wildlife Foundation conservation enterprise model aims to improve the quality of life of local communities and encourage positive local attitudes to conservation; yet, this has not been tested. This research adopted one-on-one structured questionnaire interviews to examine community and tourism lodge staff's attitudes towards conservation of, and tourism in, protected areas in two case-study sites in rural Botswana and Rwanda. Findings indicate that at both case-study sites lodge staff and the local community were generally supportive of conservation, and had positive attitudes towards conservation and tourism.